An investigation of rhetorical devices in Donald Trump’s speeches. - Trần Thị Thu (Trường Đại học Ngoại ngữ, Đại học Đà Nẵng, 2024)
This study aims at investigating Rhetorical Devices applied and their respective functions in political speeches by Donald Trump. As for each category, there will be one or more specific figures of speech to be discussed. Its purpose is to provide learners of English with practical information and to raise their awareness of Rhetorical Devices in political speeches in English